Digital Financial Inclusion, Poverty, and Income Inequality: A Bibliometric Analysis of Research Trends and Future Directions - Amaluddin Amaluddin; Teddy Christianto Leasiwal; Ali Tutupoho (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2026)
ABSTRACT The main objective of this study is to map scholarly articles on the area of the role of digital financial inclusion in addressing poverty and income inequality, and to establish an analytical framework of current developments, emerging trends, and future directions. This study employs a comprehensive bibliometric analysis, which includes bibliographic coupling and co-word analysis to develop an analytical framework that captures recent developments, prevailing trends, and future directions in this field. The current themes identified through bibliographic coupling highlighted that digital financial inclusion is recognized as a crucial driver in addressing poverty and economic income inequality through Fintech innovation. Co-word analysis confirmed these themes with four keyword clusters highlighting mobile innovation for poverty alleviation, the role of digital finance in reducing income inequality, the integration of digital inclusion into the financial system, and the economic aspects and humanitarian challenges in addressing poverty.